Co-expression With Replicating Vector Overcoming Competitive Effects Derived by a Companion Protease Inhibitor in Plants - Ma, Jiexue; Ding, Xiangzhen; Li, Zhiying; Wang, Sheng (Frontiers in Plant Science, 2021)
Plant-based expression platforms are currently gaining acceptance as a viable alternative for the production of recombinant proteins (RPs), but RPs degradation by proteases in cells hinders their superb potentials. Co-expression of a protease inhibitor (PI) shows promise as a strategy to prevent RP from proteolytic degradation in plants. However, competitive effects behind the PI-RP co-expression system may mask or obfuscate the in situ protective effects of a companion PI. Here, we explored the competitive effects by co-expressing Reteplase (rPA) with three unrelated PIs (NbPR4, HsTIMP, or SlCYS8) in Nicotiana benthamiana leaves. Remarkably, the accumulation of rPA was significantly repressed by each of the three PIs, suggesting that the competitive effects may be common among the PIs. The repression can be attenuated by reducing the PI inoculum dose in the co-inoculation mixtures, showing a negative correlation between the PI abundance of the PI-RP system and competitive effects. Interestingly, when a replicating vector was used to modulate the relative abundance of PI and RP in vivo, rPA was still boosted even at the maximal testing dose of PI, indicating that the competitive effects reduced to an ignorable level by this in vivo approach. Furthermore, a 7- to 12-fold increase of rPA achieved, proving that it is a useful way for stimulating the potentials of a companion PI by overcoming competitive effects. And this approach can be applied to molecular farming for improving the RP yields of plant expression systems.